2020
DOI: 10.20884/1.jm.2020.15.2.540
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Curcuminoid from Curcuma xanthorrhiza and Its Activity Test as Antioxidant and Antibacterial

Abstract: Curcuminoids are the main component found in many Zingiberaceae family plants. The aim of this study was to characterize curcuminoid and its activity test as an antioxidant and antibacterial. Dryed powder of C. xanthorrhiza (1 kg) was macerated with ethanol for 24 hours at room temperature. Ethanol extract of C. xanthorrhiza was subsequently fractionated with n-hexane and chloroform to take the yellow or orange indicated contain of curcuminoids. Analysis of total phenolic levels was carried out by the Follin-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In addition, C. xanthorrhiza it is also used as an ingredient in jamu (Indonesian herbal supplements and medicines). Several studies reported the pharmacological activity of C. xanthorrhiza namely as anticancer (Indrayanti et al 2021), antimicrobial (Akarchariya et al 2017), anti-inflammatory (Devaraj et al 2010), antitumor (Rahmat et al 2021), antibacterial (Atun et al 2020), antihypertensive (Campos et al 2008;Oon et al 2015), antihyperglycemic (Kim et al 2014), nephroprotective (Kim et al 2005), and antioxidant activities (Rosidi et al 2016). The active compounds influence this pharmacological effect in the rhizome of Curcuma xanthorrhiza Roxb, namely curcuminoid, which also gives a yellowish-orange color to the rhizome of C. xanthorrhiza (Erpina et al 2017) and xanthorrhizol which belongs to the sesquiterpenoid class (Susanto et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, C. xanthorrhiza it is also used as an ingredient in jamu (Indonesian herbal supplements and medicines). Several studies reported the pharmacological activity of C. xanthorrhiza namely as anticancer (Indrayanti et al 2021), antimicrobial (Akarchariya et al 2017), anti-inflammatory (Devaraj et al 2010), antitumor (Rahmat et al 2021), antibacterial (Atun et al 2020), antihypertensive (Campos et al 2008;Oon et al 2015), antihyperglycemic (Kim et al 2014), nephroprotective (Kim et al 2005), and antioxidant activities (Rosidi et al 2016). The active compounds influence this pharmacological effect in the rhizome of Curcuma xanthorrhiza Roxb, namely curcuminoid, which also gives a yellowish-orange color to the rhizome of C. xanthorrhiza (Erpina et al 2017) and xanthorrhizol which belongs to the sesquiterpenoid class (Susanto et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…is a medicinal plant of the rhizome family (Zingiberaceae), a popular ingredient used for seasoning and medicine. Curcuma contains curcuminoid fraction yield at the level of 10.06% from the ethanol extract (Atun et al, 2020), which generates a yellow color in the rhizome and exhibits several properties, such as antibacterial, anticancer, antitumor, and antiinflammation, as well as antioxidant and hypocholesterolemia (Lee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…C. xanthorrhiza is often used in combination with other medicinal plants to form a mixture of herbal products to increase stamina and immunity. [ 1 ] The potential pharmacological activities of C. xanhtorrhiza include antibacterial, antioxidant,[ 2 ] anti-inflammatory, anticancer,[ 3 ] antihypertensivity, and immunomodulatory activity. [ 4 ] The phytochemical profile obtained from various literature indicate the presence of xanthorrhizol compounds, which are typical compounds of C. xanthorrhiza , amino acids, carbohydrates, curcuminoid compounds such as octahydrocurcumin, curcumin, dihydrocurcumin, and hexahydrocurcumin,[ 1 , 5 ] and vanillin compounds[ 6 ] such as isoborneol, camphor, and trans-caryophyllene.…”
Section: Introductionmentioning
confidence: 99%